2005
DOI: 10.1529/biophysj.105.068114
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Space Diffusion in Central Nervous System: Anisotropic Diffusion Measured by Elliptical Surface Photobleaching

Abstract: Diffusion in the extracellular space (ECS) is crucial for normal central nervous system physiology. The determinants of ECS diffusion include viscous interactions with extracellular matrix/plasma membranes ("viscosity") and ECS geometry ("tortuosity"). To resolve viscosity versus tortuosity effects, we measured direction-dependent (anisotropic) diffusion in ECS in mouse spinal cord by photobleaching using an elliptical spot produced by a cylindrical lens in the excitation path. Anisotropic diffusion slowed flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…2). Confocal images of live retinal tissue slices loaded with calcein, a polar fluorescene derivative with virtually no tendency to bind cell structures or membranes (15), or transgenic frogs expressing GFP monomers or concatemers in rods, revealed that the relative concentration of soluble proteins in the outer segments was indeed molecular size dependent ( Fig. 2 B and C).…”
Section: Access Of Soluble Molecules To the Rod Outer Segment Is Steeplymentioning
confidence: 99%
“…2). Confocal images of live retinal tissue slices loaded with calcein, a polar fluorescene derivative with virtually no tendency to bind cell structures or membranes (15), or transgenic frogs expressing GFP monomers or concatemers in rods, revealed that the relative concentration of soluble proteins in the outer segments was indeed molecular size dependent ( Fig. 2 B and C).…”
Section: Access Of Soluble Molecules To the Rod Outer Segment Is Steeplymentioning
confidence: 99%
“…Experimental data suggesting that AQP4 facilitates fluid exchange between CSF and ISF are intriguing but difficult to interpret because of baseline differences in parenchymal extracellular volume fraction between wild type and AQP4-null mice [10, 11]. Quantitative studies have failed to find evidence for directional convective flow in cortical gray matter under normal conditions [12, 13], so perhaps the results of Iliff et al . [4] are a consequence of differences in extracellular space (ECS) structure between wild type and AQP4-null mice.…”
mentioning
confidence: 99%
“…where F 0 is the fluorescence intensity before photobleaching, F(0) represents the fluorescence intensity immediately after photobleaching, F(∞) is the fluorescence intensity at the time when recovery is complete, K is a parameter related to bleaching depth, α is a parameter describing the motion of molecules (α = 1 for free diffusion and α < 1 for anomalous diffusion), R is the mobile fraction, and τ = w 2 /4D is the characteristic diffusion time [6,9,15], where w is the radius of the laser beam and D is the diffusion coefficient.…”
Section: Theory Of Frapmentioning
confidence: 99%
“…Axelrod et al [6] described the mathematical modeling of FRAP and quantitatively measured the diffusion of biomolecules on a cell membrane. The FRAP technique has been used to measure the diffusion of macromolecules in biological media such as bacterial biofilm [7], articular cartilage [8], and extracellular space of brain and spinal cord in living mice [9]. The FRAP technique can also be applied to tissueengineering research, because spatial and temporal distributions of growth factor are recognized as crucial factors in controlling the differentiation and growth of specific types of cells [10].…”
mentioning
confidence: 99%